2021
DOI: 10.3389/fbioe.2021.675364
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Applications of Eggshell: Recent Advances

Abstract: The eggshell (ES) provides protection against pathogenic and physical insults while supplying essential metabolic and nutritional needs for the growing avian embryo. It is constituted mainly of calcium carbonate arranged as calcite crystals. The global chicken egg production in 2018 was over 76.7 million metric tons. In industrialized countries, about 30% of eggs are processed at breaker plants that produce liquid egg products and large quantities of solid ES waste. ES waste is utilized for a variety of low-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 50 publications
(86 reference statements)
0
21
0
2
Order By: Relevance
“…On the one hand, it is recognized that the worldwide cement consumption is more than 4 billion tons (in 2020) [84] and eggshell can also be applied in other distinctive industrial applications [85,86]. On the other hand, it is believed that there exists feasible accountability to propose and adequate planning of the certain portion of the global chicken egg production (~80 million metric tons [86,87]) to be utilized in civil engineering (replacing structural concrete or cement paste applications since minimal compressive strength is attained).…”
Section: Sem Micrograph Observationsmentioning
confidence: 99%
“…On the one hand, it is recognized that the worldwide cement consumption is more than 4 billion tons (in 2020) [84] and eggshell can also be applied in other distinctive industrial applications [85,86]. On the other hand, it is believed that there exists feasible accountability to propose and adequate planning of the certain portion of the global chicken egg production (~80 million metric tons [86,87]) to be utilized in civil engineering (replacing structural concrete or cement paste applications since minimal compressive strength is attained).…”
Section: Sem Micrograph Observationsmentioning
confidence: 99%
“…Among various poultry wastes, eggshells have been of great interest in developing eggshell composites. The eggshells contain approximately 96% calcium carbonate and other organic materials [ 53 ]. Dayanidhi et al [ 54 ] recently developed a colorimetric detector naturally derived from unmodified eggshell powder.…”
Section: Application Of Natural-derivedmentioning
confidence: 99%
“…To enhance its solubility, WCES can be treated and dissolved into acetic acid to convert it into liquid as organic fertilizer. Besides, new methods for the conversion and application of CaCO 3 derived from crushed WCES as organic fertilizers for various plants have been patented lately and documented in the literature [128]. The outcomes of the application of crushed WCES as organic fertilizer for cayenne pepper, cowpea, and sweet basil showed that the plants performed better in terms of growth, root length, and leaf quality more than the plants where commercial fertilizer was applied (Table 7).…”
Section: Agricultural Applicationsmentioning
confidence: 99%